Want to Be a Country Teacher? No, I Am Too Metrocentric - Allen M. Campbell; Gregory C. R. Yates (Journal of Research in Rural Education, 2011)
Within the city-state of South Australia, the problem of attracting teachers to teach in rural schools is of long standing. We propose that "metrocentricity" can be viewed as a personal trait inhibiting teachers from considering country positions. In this project, 148 preservice teachers responded to an online survey concerning their desire to teach in the country after graduation. Twenty three per cent indicated this was their intention, and an additional 37% were undecided. Desire to teach in the country was predicted by being schooled in the country as a child, but path modelling revealed this relationship was fully mediated by the participants' self-ratings on a scale of personal metrocentricity, described as personal identification with the city. Metrocentricity predicted desire to teach in the country even within the subgroup of individuals not schooled in the country. Metrocentricity also predicted the disposition to endorse more negative aspects of country teaching experience, and fewer positive aspects, as indexed on checklists, and these measures were found to stand as significant mediators within the descriptive partial least squares path models.